PENGARUH KINERJA LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN DAN MINAT BELI ULANG PADA MASKAPAI PENERBANGAN PT. CITILINK INDONESIA DI PEKANBARU - Agustin Anggi; Alwie Furwanti Alvi; Rahayu Danar Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Service Performance and Price Perception on Customer Satisfaction and Repurchase Intention of PT. Citilink Indonesia in Pekanbaru. The population in this study includes customers who use the airline services of PT. Citilink Indonesia in Pekanbaru, amounting to 105 people. The samples were determined by using purposive sampling method. In this study, the sample studied used a questionnaire as an instrument to prove the results of the study, for testing the hypothesis in the study using the path analysis method (path analysis) with the help of the SPSS program. The results show that: 1) There is a significant effect of Service Performance on Customer Satisfaction at PT. Citilink Indonesia in Pekanbaru, 2) There is a significant effect of Price Perception on Customer Satisfaction at PT. Citilink Indonesia in Pekanbaru, 3) There is a significant effect of Service Performance on Repurchase Intention at PT. Citilink Indonesia in Pekanbaru, 4) There is a significant effect of Price Perception on Repurchase Intention in the airline PT. Citilink Indonesia in Pekanbaru, 5) There is a significant effect of Customer Satisfaction on Repurchase Intention in the airline PT. Citilink Indonesia in Pekanbaru, 6) There is no significant effect of Service Performance on Repurchase Intention through Customer Satisfaction on the airline PT. Citilink Indonesia in Pekanbaru, 7) There is no significant effect of Price Perception on Repurchase Intention through Customer Satisfaction on the airline PT. Citilink Indonesia in Pekanbaru.Keywords: Service Performance, Price Perception, Customer Satisfaction, Repurchase Intention